2015
DOI: 10.1097/ico.0000000000000463
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Corneal Deformation and Ease of Lenticule Separation From Residual Stroma in Small Incision Lenticule Extraction

Abstract: CD was inversely correlated with the ease of lenticule separation from the residual stroma and may assist in customization of the energy parameters of the laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Inclusion criteria were patients undergoing 6-month follow-up after the procedure with preoperative spherical equivalent (SE) between -1 D and -7 D and astigmatism under 3.5 D, stable myopia for at least 1 year before surgery, and CDVA of 20/25 or better. Exclusion criteria were pregnancy at time of surgery or follow-up, a preoperative central corneal thickness of less than 480 µm, an expected postoperative residual stromal bed of less than 250 µm, topographic map compatible with subclinical keratoconus or other ectatic corneal disorder, and any other ocular disease for which laser refractive surgery procedures are not indicated (15). The procedure was explained to all the patients who signed the preoperative informed consent, and the study complied with the tenets of the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria were patients undergoing 6-month follow-up after the procedure with preoperative spherical equivalent (SE) between -1 D and -7 D and astigmatism under 3.5 D, stable myopia for at least 1 year before surgery, and CDVA of 20/25 or better. Exclusion criteria were pregnancy at time of surgery or follow-up, a preoperative central corneal thickness of less than 480 µm, an expected postoperative residual stromal bed of less than 250 µm, topographic map compatible with subclinical keratoconus or other ectatic corneal disorder, and any other ocular disease for which laser refractive surgery procedures are not indicated (15). The procedure was explained to all the patients who signed the preoperative informed consent, and the study complied with the tenets of the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…As SMILE essentially retains the anterior stromal architecture, it would be expected that the strongest part of the cornea will continue to contribute and maintain its strength post‐operatively. Of interest, Shetty et al recently described a relationship between corneal deformation and the ease of lenticule separation. Against this, Agca et al found no difference between LASIK and SMILE cohorts in terms of biomechanical parameters.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Small OZ leaves limited space for morphological adaptation. In addition, biomechanical weakening of the cornea indicates less resistance to corneal deformation (18). We suspect that the correction of more severe myopia, accompanied by thicker lenticule and thinner RBT, makes it more difficult to retain corneal biomechanics or maintain corneal shape.…”
Section: Discussionmentioning
confidence: 98%